Tempted : an It Girl novel - Von Ziegesar, Cecily (New York : Little, Brown and Co., 2008)
Beginning with Waverly Academy's annual Halloween ball, Jenny, who is still seeking her mysterious benefactor, watches her own popularity soar as Tinsley's plummets, while Callie finds herself at a Maine "health spa."
"Poppy."
Includes excerpt from: Gossip girl : the Carlyles.
Keywords: Conduct of life -- Fiction; Interpersonal relations -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Arson -- Fiction; Private schools -- Fiction; Popularity -- Fiction; Wealth -- Fiction; Dating (Social customs) -- Fiction; Popularity -- Fiction; Interpersonal relations -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Halloween -- Fiction; New York (State) -- Fiction; New York (State) -- Fiction